Mantle Cell Lymphoma of the Prostate Gland Treated with Holmium Laser Enucleation. Issue 3 (1st July 2017) - Milburn, Preston A.; Cable, Christian T.; Trevathan, Sean; El Tayeb, Marawan M. El
Abstract : Mantle cell lymphoma of the prostate is rare and is seldom encountered in general urologic practice. It either arises primarily from the prostate or is a result of metastatic spread from another site. This specific type of lymphoma has an aggressive course and may respond poorly to traditional chemotherapy with frequent relapses. Mantle cell lymphoma occurs in middle age or older, which is also when symptoms of benign prostatic enlargement begin in men. This overlap makes the diagnosis of lymphoma of the prostate difficult and makes the treatment more complex. We describe a case of mantle cell lymphoma of the prostate that caused significant enlargement and bladder outlet obstruction with urinary retention. The obstruction was treated with holmium laser enucleation of the prostate with good functional results.